Komodifikasi Anak Dalam Program Acara Reality Show Di Trans Tv - Agustinus Kardiman; Haryo Windratno (Inter Komunika, 2016)
This research is attempted to uncover forms, processes and ideologies associated with the commodification of children at those impressions by takes perspective of a critical discourse analysis of the commodification of children in the program "Janji Suci Raffi and Gigi" produced by Trans TV. Analysis used is critical discourse analysis Norman Fairclough. Fairclough critical discourse analysis is done in three stages: (1) analysis of texts; (2) the practice of discourse and (3) the practice of social culture. Based on discoveries of the analysis of texts Program "Janji Suci Raffi and Gigi", interviews with several sources and combined with the relevant libraries show that: (1) occurs commodification of children in the show program "Janji Suci Raffi and Gigi" in Trans TV; (2) The commodification of children occurs through the formation process of setting and moments by the production crew and Raffi through Rafatar to show patterns and behaviors as a toddler; (3) The ideology behind the process of commodification of children is a capitalist ideology. The capitalist ideology in Trans TV due to Trans TV is a private broadcasting media who have the goal of business and profit.